Intrinsic Nano-Ductility of Glasses: The Critical Role of Composition - Wang, Bu; Yu, Yingtian; Lee, Young Jea; Bauchy, Mathieu (Frontiers in Materials, 2015)
Understanding, predicting and eventually improving the resistance to fracture for silicate materials is of primary importance to design tougher new glasses suitable for advanced applications. However, the fracture mechanism at the atomic level in amorphous silicate materials is still a topic of debate. In particular, there are some controversies about the existence of ductility at the nanoscale during crack propagation. Here, we present simulations of fracture of three archetypical silicate glasses, using molecular dynamics. The simulations clearly show that, depending on their composition, silicate glasses can exhibit different degrees of ductility at the nanoscale. Additionally, we show that the methodology used in the present work can provide realistic predictions of fracture energy and toughness.